Post Covid-19 Emergency Mitigation Strategies Through Parents Readiness in Children's Behavior and Social Development - Merina, Nuning Dwi Merina; Rahmawati, Iis; Sulistyorini, Lantin; Afdi Septiyono, Eka (Jurnal Kesehatan dr. Soebandi, 2023)
The COVID-19 pandemic has an impact on patterns of social interaction, education, and behavior on child development. Children with social development problems need good readiness from their parents in order to carry out their optimal growth functions. Parental readiness is one of the mitigation strategies to reduce the negative impact of COVID-19. The purpose of this research is to explore how parents are prepared for their children's social development after the COVID-19 emergency, in the Jember Regency. This research method uses qualitative research with a phenomenological design involving 7 parents in the Jember Regency area. The research instrument used a design theory from Prochaska, namely the transtheoretical model for parental preparation and Hurlock's theory, namely the ability to behave in accordance with social demands for children's social development. Data analysis used the induction method with specific conclusions drawn for the general public and presented descriptively. Parents have prepared and facilitated children's needs, learning environment, and provided motivation to children in their development period. Some parents admit that they have difficulty adjusting to their child's development. This is different from parents as housewives who have a lot of time with their children who claim that they understand their child's condition and can adapt to their child's development. Parents also provide time for their children to talk about their activities in their environment and limit their use of gadgets and replace them with other games that can stimulate their motor and sensory. The readiness of parents in the social development of children in the post-COVID-19 emergency shows positive results. Parents are well prepared to support their children's social development. Keywords: Child, COVID-19, Development, Parent, Readiness.